PERANCANGAN DAN IMPLEMENTASI PROGRAM KENDALI OTOMATIS PADA SISTEM PENGEPAKAN BUAH MENGGUNAKAN PLC - Zahrul Ulum; Tunggul Parningotan Hutapea; Awaluddin Sitorus; Aliman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to design and implement an automatic control program for a fruit packaging system using a Programmable Logic Controller (PLC) to improve efficiency, accuracy, and consistency in the packaging process. Manual fruit packaging often results in several problems, including inconsistent product quantities, longer processing times, and a higher risk of human error. These issues can reduce productivity and affect the quality of packaged products. The research employed an engineering research method with an experimental approach consisting of system design, ladder diagram programming, prototype development, and system testing. The main controller used was an Omron CP1E-E30SDR-A PLC programmed using CX-Programmer version 9.7 software. The system was designed with switches acting as simulated sensors and indicator lamps serving as simulated actuators. The operational sequence begins with empty carton detection, followed by fruit filling until the predetermined quantity is reached, automatic conveyor stopping, and automatic carton replacement without operator intervention. Furthermore, a buzzer was incorporated as a warning indicator for abnormal conditions such as carton unavailability, fruit shortages, or carton accumulation. The testing results demonstrated that the system operated according to the designed control logic, achieved high accuracy in fruit counting, and effectively controlled the carton replacement process automatically. Therefore, the PLC-based automatic control system can improve the effectiveness, efficiency, and reliability of fruit packaging operations and has strong potential for implementation in larger industrial applications.